2010
DOI: 10.1038/gt.2010.18
|View full text |Cite
|
Sign up to set email alerts
|

An ex vivo loop system models the toxicity and efficacy of PEGylated and unmodified adenovirus serotype 5 in whole human blood

Abstract: Polyethylene glycol coating (PEGylation) of adenovirus serotype 5 (Ad5) has been shown to effectively reduce immunogenicity and increase circulation time of intravenously administered virus in mouse models. Herein, we monitored clot formation, complement activation, cytokine release and blood cell association upon addition of uncoated or PEGylated Ad5 to human whole blood. We used a novel blood loop model where human blood from healthy donors was mixed with virus and incubated in heparin-coated PVC tubing whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…29 However, studies on Ad5 interaction in human blood indicate that binding to erythrocytes has a greater role than interaction with blood coagulation factors. 24,30 Moreover, data from clinical trials strongly indicate that systemic administration of Ad5 do not affect the liver to the same extent as has been observed in mouse models. 30,31 Treatment with oncolytic Ads has been well tolerated and more importantly no significant liver toxicity has been reported to date after Ad infusions including numerous injections directly into the hepatic artery.…”
Section: Oncolytic Adenovirus With Somatostatin Motifs J Leja Et Almentioning
confidence: 83%
See 2 more Smart Citations
“…29 However, studies on Ad5 interaction in human blood indicate that binding to erythrocytes has a greater role than interaction with blood coagulation factors. 24,30 Moreover, data from clinical trials strongly indicate that systemic administration of Ad5 do not affect the liver to the same extent as has been observed in mouse models. 30,31 Treatment with oncolytic Ads has been well tolerated and more importantly no significant liver toxicity has been reported to date after Ad infusions including numerous injections directly into the hepatic artery.…”
Section: Oncolytic Adenovirus With Somatostatin Motifs J Leja Et Almentioning
confidence: 83%
“…22,23 Therefore, we evaluated the recombinant GFP-expressing, fiber-modified Ad5 vectors in a newly developed human blood loop system. 24 Viruses were mixed with whole blood or medium and incubated in heparin-coated polyvinyl chloride tubing at 37 1C while rotating. We used blood from six healthy donors (D); four with low ability to neutralize Ad5 (D1, D2, D5 and D6) and two with high neutralizing ability (D3 and D4), to study the degree of neutralization in whole blood by adding the virus/blood sample dilutions to 911 cells and measuring GFP expression the day after.…”
Section: An Fwkt-modified Ad5 Vector Is Superior To a Non-modified Vementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the data suggested that hFX binding to HAd5 did not interfere with polyclonal anti-Ad IgG binding. In human blood, elevated levels of proinflammatory cytokines can be detected within hours ex vivo (36) and in vivo (37) after systemic administration. While the TLR4 internalization is thought to be a requirement for the induction of interferon-␤ (IFN-␤) (35,38) through a TRIF/TRAF3/IRF3 pathway, the possibility of TLR4 signaling occurring directly from the cell surface and induction of proinflammatory cytokines via MyD88-NF-B cannot be formally excluded.…”
Section: Resultsmentioning
confidence: 99%
“…The DNA copy number was detected by using the primers Ad.Titration.F and Ad.Titration.R targeting the adenovirus E4 ORF1 region. Plasmid, pCR2.1(AdE4orf1), containing the same amplicon, was used for the generation of standard curve (10). Virus titer was calculated as the mean of three independent experiments.…”
Section: Methodsmentioning
confidence: 99%